2009
DOI: 10.1042/bj20081983
|View full text |Cite
|
Sign up to set email alerts
|

Copper proteins and ferroxidases in human plasma and that of wild-type and ceruloplasmin knockout mice

Abstract: In the blood plasma of humans and rats, ceruloplasmin is the major copper-binding protein and ferroxidase, accounting for 70% of the copper present in the plasma, with the rest binding primarily to albumin and a macroglobulin. Systematic studies with fresh plasma were carried out to compare what occurs in the mouse. C57BL6 mice had half as much copper and pPD (p-phenylene diamine) oxidase activity as humans and rats, 20-40% as much ferroxidase activity as humans (determined using three different assays) and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 45 publications
1
41
2
Order By: Relevance
“…It should finally be noted that copper metabolism in mice has both similarities to and differences from humans, with decreased plasma copper levels in mice, compared with humans. Differences also exist in secondary copper binding proteins but with the liver as a significant copper reservoir in both species (38,39). These data further suggest that the relationship between Cu-ATSM uptake and hypoxia is not entirely direct in vivo, in contrast to results from experiments in tissue culture.…”
Section: Discussioncontrasting
confidence: 53%
“…It should finally be noted that copper metabolism in mice has both similarities to and differences from humans, with decreased plasma copper levels in mice, compared with humans. Differences also exist in secondary copper binding proteins but with the liver as a significant copper reservoir in both species (38,39). These data further suggest that the relationship between Cu-ATSM uptake and hypoxia is not entirely direct in vivo, in contrast to results from experiments in tissue culture.…”
Section: Discussioncontrasting
confidence: 53%
“…Volume ( min and transcuprein (approximately 15% and 10% of the total Cu, respectively) (Gray et al, 2009). Seminal plasma Cu concentrations were reported to be 0.5 ppm in ram (Cole and Cupps, 1969) which were higher from the results in the current study.…”
Section: Discussioncontrasting
confidence: 37%
“…In parallel with the elevated plasma copper levels at P49 in Npc1 −/− mice, we also observed a 49 ± 4% increase (p = 0.0004) in total CP compared to WT (Figure 2D). This was also reflected in a concomitant 53 ± 7% increase (p < 0.0001)in total oxidase activity, the sum of azide-sensitive activity (attributed to CP, and known as ferroxidase I) and azide-resistant activity (ferroxidase II, which is proportionally more in mice than in humans) 36 (Figure 2E). Although there was no age-dependent change in total CP levels in Npc1 −/− mice, there was an age-dependent increase in the copper-bound active holo-CP level and a decrease in the unmetallated apo-CP level (Figure 2F).…”
Section: Resultsmentioning
confidence: 85%
“…In this study we further demonstrated that this corresponds to increased copper-bound holo-CP and CP oxidase activity (Figure 2F and 2G). This difference between human and mouse plasma CP and its oxidase activity may be explained by a species-specific difference in CP metabolism and activity 36 . In humans, CP accounts for 90 – 100% of the plasma ferroxidase activity.…”
Section: Discussionmentioning
confidence: 96%